Inculcating Multicultural Education Through the Development of Religious Culture in Junior High School (SMP) Negeri 7 Mataram - Maimun Maimun (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2020)
Multicultural education can be used as a media for the development of equal human potential, able to respect each other's differences in terms of religion, tribe, race, ethnicity, culture, and language. This study focuses on: (1) How is the concept of multicultural education through the development of religious culture in SMP Negeri 7 Mataram ?; and (2) What is the reality of multicultural education and religious culture developed in SMP Negeri 7 Mataram? This type of research is descriptive qualitative, describing the concepts and reality of the implementation of multicultural education with the development of religious culture. The results of this study are (1) The concept of Multicultural Education with the development of religious culture adapted to the vision, mission, and profile of the school that is building religious attitudes and behaviors that are reflected through cooperation, tolerance and culture in the community of school members by not ignoring religious concepts that embraced by each school citizen; and (2) The reality of multicultural education with the development of religious culture is reflected in the religious and social values ??or norms of the activities of all school members, and the availability of adequate places of worship for students who are implementing religious programs for all religious adherents.